2016
DOI: 10.21608/zvjz.2016.7872
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Insecticide "Chlorpyrifos" on Immune Response of Oreochromis niloticus

Abstract: This study was carried out to determine the level of Chlorpyrifos (CPF), an organophosphorus insecticide, in water of Abbassa and Sahl El-Hussinia fish farms and investigate the sub lethal concentration of this pesticide on immune response of Oreochromis niloticus (O. niloticus). Water samples were collected from Abbassa and Sahl El-Hussinia fish farms and analyzed using Gas chromatograph (GC) for detection of Chlorpyrifos level. Two hundred and ninety O. niloticus with average body weight (35±0.5 g) were coll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 16 publications
1
5
0
Order By: Relevance
“…The elevation of mortality rate may be due to toxic effect of chlorpyrifos. Similar results were recorded by El-Bouhy et al [25] who reported that Nile tilapia showed fin rot, rapid movement of operculum with opened mouth and collection of fish near water surface when exposed to chlorpyrifos insecticide.…”
Section: Chronic Exposure Assay and Clinical Observationssupporting
confidence: 89%
“…The elevation of mortality rate may be due to toxic effect of chlorpyrifos. Similar results were recorded by El-Bouhy et al [25] who reported that Nile tilapia showed fin rot, rapid movement of operculum with opened mouth and collection of fish near water surface when exposed to chlorpyrifos insecticide.…”
Section: Chronic Exposure Assay and Clinical Observationssupporting
confidence: 89%
“…In the present study, significant elevations in relative expression of interleukin 1 beta (IL-1β) gene were recorded in liver, muscle and brain of treated group compared to control. Up-regulation of interleukin-1β was previously reported in Nile tilapia intoxicated with chlorpyrifos (El-Bouhy, El-Nobi, Reda, & Ibrahim, 2016) and in zebrafish by cisbifenthrin (Jin, Pan, Cao, Ma, & Fu, 2013). Cyclooxygenase 2 (COX-2), induced by proinflammatory stimuli, cytokines, hormones and growth factors, is an important source of prostaglandin formation in inflammation (Cryer & Feldman, 1998).…”
Section: Expression Findings Of Il-1β and Cox-2 Genesmentioning
confidence: 92%
“…In line with this, malathion has a negative effect on the innate immune response (WBC, ROS production, and phagocytic activity) in C. carpio carpio [ 75 ]. Additionally, acute and chronic exposure to chlorpyrifos effects leukocyte phagocytic capacity [ 76 , 77 , 78 ]. Furthermore, malathion reduces the phagocytic capacity of Murray codfish ( Maccullochella peelii T. L. Mitchell) [ 79 ].…”
Section: Op-mediated Modulation Of the Immune Responsementioning
confidence: 99%